2005
DOI: 10.1243/095440705x34946
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of seat backrest angle and neck injury in low-velocity rear impacts

Abstract: Car-rear-impact-induced cervical spine injuries present a serious burden on society and, in response, seats offering enhanced protection have been introduced. Seats are evaluated for neck protection performance but only at one specific backrest angle, whereas in the real world this varies greatly owing to the variation in occupant physique. Changing the backrest angle modifies the seat geometry and thereby the nature of its interaction with the occupant.Low-velocity rear-impact tests on a BioRID II anthropomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
6
2
Order By: Relevance
“…However, a controlled biomechanical investigation of these factors is required to delineate their effects. Although lower neck shear force proved to be sensitive to changes in seatback orientation (Latchford et al 2005) and occupant orientation relative to the seatback (Benson et al 1996;Sundararajan et al 2004) in the present and previous investigations, trends were somewhat contradictory. Present results are supported by Benson et al (1996) in that higher shear forces resulted when occupants were seated more vertically relative to the seat, whereas Latchford et al (2005) reported decreased shear forces for more vertically oriented seatbacks.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…However, a controlled biomechanical investigation of these factors is required to delineate their effects. Although lower neck shear force proved to be sensitive to changes in seatback orientation (Latchford et al 2005) and occupant orientation relative to the seatback (Benson et al 1996;Sundararajan et al 2004) in the present and previous investigations, trends were somewhat contradictory. Present results are supported by Benson et al (1996) in that higher shear forces resulted when occupants were seated more vertically relative to the seat, whereas Latchford et al (2005) reported decreased shear forces for more vertically oriented seatbacks.…”
Section: Discussioncontrasting
confidence: 70%
“…Although lower neck shear force proved to be sensitive to changes in seatback orientation (Latchford et al 2005) and occupant orientation relative to the seatback (Benson et al 1996;Sundararajan et al 2004) in the present and previous investigations, trends were somewhat contradictory. Present results are supported by Benson et al (1996) in that higher shear forces resulted when occupants were seated more vertically relative to the seat, whereas Latchford et al (2005) reported decreased shear forces for more vertically oriented seatbacks. Increased facet joint ligament strains for more vertical seating positions obtained during the computational part of the present study are supported by facet joint stretch magnitudes in PMHS reported by Sundararajan et al (2004) and indicate increased injury risk for more vertical seating positions.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations